Answer:
Option A. Divide 382 by 1027.
Step-by-step explanation:
A survey was done about the people who preferred running indoors and outdoors. Then a two way table was prepared.
Amir is making a relative frequency table.
As we know relative frequency table is prepared by the dividing number of frequency by the total number of students taken in the sample.
Now he will take the data from the given two way table.
People age 30 years and younger were 382 running outdoors and 105 running indoor.
So people having age 30 and below are 382 + 105 = 487
Similarly people Over 30 years old running outdoor and indoor = 299 + 241 = 541
Now Total number of people taken in the sample = 487 + 541 = 1027
So relative frequency for the people of age 30 and younger will be
382/1027 for outdoor and 105/1027 for indoor.
Therefore answer will be Option A. Divide by 382/1027.
Her mistake is that she did the change in x over the change in y. It should be the change in y over the change in x. So: -2-3/-2-4
Isosceles trapezoid
<ONM = <LON = 100
<OLM = <NML = 1/2(360 - 2(100))
= 1/2(360 - 200)
= 1/2(160)
= 80
Answer
<OLM = 80 degress
The answer is the crab and the bird are 180 feet apart
Here we will use the trial and error method.
- We will try putting different values of x.
<h3 /><h3>1st of all</h3><h3>x=1</h3>
![\begin{gathered}\\ \sf\longmapsto 1(1-3)+1-3=0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%201%281-3%29%2B1-3%3D0%5Cend%7Bgathered%7D)
![\begin{gathered}\\ \sf\longmapsto (-2)+1-3=0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%20%28-2%29%2B1-3%3D0%5Cend%7Bgathered%7D)
![\begin{gathered}\\ \sf\longmapsto -2+1-3=0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%20-2%2B1-3%3D0%5Cend%7Bgathered%7D)
![\begin{gathered}\\ \sf\longmapsto -2-2=0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%20-2-2%3D0%5Cend%7Bgathered%7D)
![\begin{gathered}\\ \sf\longmapsto -4≠0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%20-4%E2%89%A00%5Cend%7Bgathered%7D)
<h2>Now,</h2><h3>x=2</h3>
![\begin{gathered}\\ \sf\longmapsto 2(2-3)+2-3=0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%202%282-3%29%2B2-3%3D0%5Cend%7Bgathered%7D)
![\begin{gathered}\\ \sf\longmapsto 2(-1)+2-3=0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%202%28-1%29%2B2-3%3D0%5Cend%7Bgathered%7D)
![\begin{gathered}\\ \sf\longmapsto -2+2-3=0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%20-2%2B2-3%3D0%5Cend%7Bgathered%7D)
![\begin{gathered}\\ \sf\longmapsto -3≠0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%20-3%E2%89%A00%5Cend%7Bgathered%7D)
<h2>Again,</h2><h3>x=3</h3>
![\begin{gathered}\\ \sf\longmapsto 3(3-3)+3-3=0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%203%283-3%29%2B3-3%3D0%5Cend%7Bgathered%7D)
![\begin{gathered}\\ \sf\longmapsto 3(3-3)=0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%203%283-3%29%3D0%5Cend%7Bgathered%7D)
![\begin{gathered}\\ \sf\longmapsto 3×0=0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%203%C3%970%3D0%5Cend%7Bgathered%7D)
![\begin{gathered}\\ \sf\longmapsto 0=0\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5C%5C%20%5Csf%5Clongmapsto%200%3D0%5Cend%7Bgathered%7D)
<h3>☣Hence, The value of X as 3 satisfies the equation!</h3>